Analisa Kadar Antosianin pada Bunga Telang sebagai Antibakteri dengan Metode Maserasi - Rusnia Junita Hakim; Dina Adelina; Zakki Rosmi Mubarok; Radita Mellya Yolandari; Khana Aulia Romli (Politeknik Negeri Lhokseumawe, 2026)
Anthocyanins are natural flavonoid pigments widely recognized for their biological activities, including antibacterial properties. Butterfly pea (Clitoria ternatea L.) flowers are known to contain significant levels of anthocyanins; however, the influence of extraction parameters on anthocyanin yield and their correlation with antibacterial activity remains limited. This study aimed to evaluate the effect of ethanol concentration (75%, 80%, and 90%) and maceration time (8, 16, and 24 hours) on total anthocyanin content of fresh butterfly pea flowers and to assess their antibacterial activity. Anthocyanin content was determined using the pH differential method with UV–Vis spectrophotometry at 510 nm and 700 nm. Extraction yield and physicochemical characteristics (pH, viscosity, and density) were also analyzed. The highest extraction yield (1.64%) was obtained using 75% ethanol for 8 hours, while the highest anthocyanin content (1.071 mg/100 g) was achieved with 80% ethanol for 8 hours, corresponding to absorbance values of 1.3425 (pH 1.0) and 1.3365 (pH 4.5). These results indicate that solvent polarity significantly influences anthocyanin extraction efficiency. However, antibacterial testing against Staphylococcus sp. showed only limited inhibition zones under all treatment conditions, suggesting that the extract concentration did not reach the minimum inhibitory concentration (MIC). Overall, while extraction parameters significantly affected anthocyanin content, increased anthocyanin levels did not directly correspond to significant antibacterial activity.